2002
DOI: 10.1067/mva.2002.128303
|View full text |Cite
|
Sign up to set email alerts
|

The Carotid Surgery for Ischemic Stroke trial: A prospective observational study on carotid endarterectomy in the early period after ischemic stroke

Abstract: Early CEA within 6 weeks after a carotid-related ischemic stroke can be performed with a perioperative stroke or mortality rate comparable with the results reported in the European Carotid Surgery Trial and the North American Symptomatic Carotid Endarterectomy Trial. The risk of parenchymatous bleeding is low. ASA grades III and IV and decreasing age were predictive of an increased perioperative risk, especially if CEA was performed within the first 3 weeks. Patients at low risk can undergo operation safely wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
56
1
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 0 publications
2
56
1
4
Order By: Relevance
“…Moreover, ADC lesions were shown to normalize more often within three hours after stroke onset as compared to the three-to six-hour time window, particularly when they were accompanied by a smaller perfusion lesion (15,21). However, there are acute patients with a persisting perfusion-diffusion mismatch who benefit from immediate carotid artery surgery both clinically and in terms of cerebral perfusion (46,47). Similarly, Desmoteplase was shown to be an effective thrombolytic treatment during the three-to six-hour window in patients with acute stroke and a perfusion-diffusion mismatch (48).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ADC lesions were shown to normalize more often within three hours after stroke onset as compared to the three-to six-hour time window, particularly when they were accompanied by a smaller perfusion lesion (15,21). However, there are acute patients with a persisting perfusion-diffusion mismatch who benefit from immediate carotid artery surgery both clinically and in terms of cerebral perfusion (46,47). Similarly, Desmoteplase was shown to be an effective thrombolytic treatment during the three-to six-hour window in patients with acute stroke and a perfusion-diffusion mismatch (48).…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 7 papers reported risks in older patients but did not compare their results to younger patients in the same centre(s) and were therefore excluded. Among the 62 remaining eligible papers [35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89, 90, 91, 92, 93, 94, 95, 96, 97], there were no differences in the associations between either age or sex and overall 30-day stroke rate, death rate or combined stroke and death rate between studies reporting the associations as their primary aim and those which reported them as a subanalysis along with other risk factors (fig. 1, 2) and so data from both types of study are combined in the analyses below.…”
Section: Resultsmentioning
confidence: 99%
“…The actual timing of CEA does not seem to influence the complication rate [1,14,15,16]. Following the recommendations from a meta-analysis, the procedure should ideally take place within 2 weeks after onset of symptoms [6].…”
Section: Discussionmentioning
confidence: 99%